Spatially Controlled Embedded Bioprinting of Prevascularized Spheroids‐Containing Biopatch Enables Functional Skin Regeneration - Minjun Ahn; Gyu Tae Park; Dongjun Lee; Sik Yoon; Sae‐Ock Oh; Jae Ho Kim; Byoung Soo Kim (Advanced Healthcare Materials, 2026)
ABSTRACT Functional vascularization remains a critical challenge in the regeneration of full‐thickness skin defects. Here, we present a 3D embedded bioprinting strategy for engineering vascularized biopatches through the precise integration of prevascularized multicellular spheroids within a skin‐derived decellularized extracellular matrix (SdECM) bioink. Rheological results reveal that a 1.0% (w/v) SdECM formulation exhibits yield‐stress behavior, pronounced shear‐thinning, and rapid shear recovery, enabling high‐fidelity of spheroids while preserving cell viability and structural integrity. Using this platform, endothelial spheroids with tunable diameters are fabricated to investigate size‐dependent vascular self‐organization. Intermediate‐sized spheroids (∼700 µm) demonstrate robust endothelial network formation, with enhanced vascular coverage, branching complexity, and angiogenic gene expression while avoiding excessive hypoxia. Spatial organization of prevascularized spheroids critically regulates paracrine‐mediated wound repair, with enhanced fibroblast migration observed when inter‐spheroid distances were within 1.8 mm. Furthermore, incorporation of mesenchymal stem cells (MSCs) provides perivascular‐like support, significantly stabilizing microvascular networks, with an optimized endothelial cell–to–MSC ratio of 1:0.5. In a full‐thickness murine wound model, multicellular spheroids‐laden SdECM biopatches significantly accelerate wound closure, enhance re‐epithelialization, promoted angiogenesis, and improve blood perfusion. Collectively, this study establishes a scalable embedded bioprinting for engineering prevascularized biopatches and provides design principles for spheroid‐based soft tissue regeneration.